Combined transcriptome, metabolome, and miRNA analysis reveals the genetic regulatory network of sweet corn pericarp thickness - Wu, Xiaming; Liu, Ruixiang; Zhang, Meijing; Yang, Min; Zhou, Chenping; Kuang, Ruibin; Chen, Yanping; Wei, Yuerong (Frontiers in Plant Science, 2025)
The thickness of the pericarp is a complex characteristic that determines sweet corn’s palatability. However, the molecular mechanisms in forming pericarp thickness differences have not been clarified. In this study, we conducted transcriptomics, miRNA analysis, and metabolomics to explore the underlying molecular mechanisms. Scanning electron microscopy (SEM) revealed that the disparity in pericarp thickness is primarily due to variations in the number of cell layers. Our combined multi-omics analysis discovered 6,054 differentially expressed genes (DEGs), 73 differentially expressed miRNAs, 113 differentially accumulated metabolites (DAMs), and several key miRNAs, such as zma-miR164, zma-miR166, zma-miR827, and zma-miR171b were identified, which modulate the expression of different transcription factors and regulate the signal transduction of various plant hormones, thereby influencing pericarp thickness. Additionally, our integrated transcriptomic and metabolomic analysis revealed that genes and metabolites involved in plant hormone signal transduction and phenylpropanoids biosynthesis pathway play a significant role in regulating pericarp growth and development. Furthermore, we observed that in the thick pericarp line (M08), the content of cytokinins was significantly reduced, while phenylpropanoid compounds such as 5-O-feruloylquinic acid glucoside, berberine, scopoletin, sinapic alcohol, sinapic acid and 3-O-feruloylquinic acid glucoside accumulated considerably. These findings provide valuable theoretical support and genetic resources.